Investigating the Influence of Approach Angle for Ceramic Cutting Tools on Chip Formation During Turning - Kidhir B.A.; Mohammed B.; Suhail A.H.; Ismail N. (2023)
In order to increase the efficiency and reduce costs it is necessary to get a better understanding of the metal-cutting process, especially the influence of chip formation on the performance of the cutting tool and quality of the surface roughness. The ultimate objective of the science of metal cutting is to solve practical problems associated with efficient material removal in the metal-cutting process. The aim of this study was to investigate the influence of approach angle on chip formation through the chip cross section area. Mild steel AISI 1020 and nickel based Hastelloy C-276 was selected as workpiece materials during this investigation in turning process. Turning computerized numerical control machine was selected for running all tests. For this study, data are selected depending on the design of experiments. Box-Behnken design selected to be three levels for each cutting parameter as cutting speed, feed rate and depth of cut. Analysis of variance as a statistical technique was used for data analysis and comparison. Results showed that chip cross section areas for both materials affected by an approach angle significantly. 2012 King Fahd University of Petroleum and Minerals.